The impact of the COVID-19 pandemic on physical activity and anxiety levels of young mental health patients and their parents - Daniel Vella Fondacaro; Francesca Vella Fondacaro; Nigel Camilleri (Hogrefe AG, 2023)
Abstract: Introduction: One restriction measure during the COVID-19 pandemic period was the closure of sport-related facilities, generating substantial anxiety. This study analyzed longitudinal changes in anxiety and physical activity (PA) levels in young people (YP) attending a community child and adolescent mental health service, and their parents/caregivers from 2020 to 2022. Method: This quantitatively driven convergent mixed-methods cohort study utilized validated scoring tools (GAD-7/GLTEQ) as the core quantitative component, and open-ended questions as the supplementary qualitative component. The quantitative and qualitative data were statistically analyzed, and both results were integrated. Questionnaires were distributed in August-October 2020 (Phase 1: At the peak of restriction period), August-October 2021 (Phase 2: During gradual removal of restrictions) and August-October 2022 (Phase 3: When all restrictions were removed). Results: Parent/caregiver's anxiety levels significantly reduced from Phase 1 to Phase 3. Results revealed non-significant improvements in YP's PA levels from Phase 1 to Phase 3. PA levels in YP were significantly higher than those of parents/caregivers throughout all Phases. A significant negative correlation was revealed between PA and anxiety levels in parents/caregivers throughout all Phases. The fear of getting infected, lifting of restrictive measures, vaccination benefits, and pandemic-induced social/financial struggles were common themes generated from the qualitative comments. Conclusion: The authors recommend PA promotional campaigns and incentives during such restrictive periods, helping the population's mental well-being. The high attrition rates in this study may decrease its generalizability. However, the results generated from this innovative study may serve as a platform for future research carried out during traumatic periods.